Structural health detection sensor based on RFID technology - Bo Wang; Yifeng Yuan; Ke Wang; Shengli Cao; Yalun Song; Male Feng (APL Materials)
In order to achieve structural health monitoring, a frequency-domain-based chipless radio-frequency identification sensor has been studied. The sensor is composed of an octagonal patch antenna and a Taconic CER-10 substrate, with overall dimensions of 24 × 24 × 1.27 mm3. Crack detection and strain detection simulations were conducted in the 3–6 and 6–12 GHz dual-frequency bands using HFSS. The results show that the sensor's resonant frequency decreases under tensile strain and increases under compressive strain. As the width, depth, and length of structural cracks increase, the sensor's resonant frequency shifts to lower frequencies. The designed structural health monitoring sensor can detect structural strain and damage with millimeter-level resolution through resonant frequency shifts. The sensor's maximum strain capacities under three different mechanical strains are −40% to 90%, −70% to 120%, and −40% to 90%, respectively. The sensor can detect changes in crack width, depth, and length without deformation, demonstrating a linear relationship between crack expansion and resonant frequency.